Blogger Sebagai Media Pembelajaran Sastra dalam Meningkatkan Kemampuan Menulis Cerpen Siswa SMA Negeri 1 Kota Serang di Era Digital - Desty Endrawati Subroto; Siti Nurelisah; Sabrinah Meilani; Nadiva Dewi Maulina (Pusat riset dan Inovasi Nasional, 2026)
The development of digital technology provides new opportunities for learning innovation, including in literature learning at Sma Negeri 1 Serang City. This study aims to describe the use of Blogger as a literature learning medium in improving short story writing skills of high school students in the digital era. This study uses a qualitative approach with descriptive methods. The subjects of the study were students of SMA Negeri 1 Serang City with a population of approximately 1,756 students who participated in short story writing learning based on Blogger as a publication and learning medium. Data collection techniques were carried out through observation, interviews, and document analysis of the results of students' short stories published on Blogger. The purpose of this study is to determine the benefits of using Blogger in literature learning to increase student learning motivation, provide space for creativity in writing, and make it easier for students to publish and share their literary works digitally. In addition, Blogger media also encourages students to be more active in the learning process because of interactions through comments and feedback from teachers and peers. Thus, the use of Blogger as a literature learning medium can be an innovative alternative in improving short story writing skills of high school students in the digital era.